On the controls of preferential flow in soils of different hillslope position and lithological origin. Issue 22 (2nd September 2020) - Tang, Qicheng; Duncan, Jonathan M.; Guo, Li; Lin, Henry; Xiao, Dacheng; Eissenstat, David M.
Abstract: Soils derived from different lithologies and their controls on preferential flow remain underexplored in forested landscapes. In the same lithology, the propensity for preferential flow occurrence at different hillslope positions also remains largely elusive. By utilizing a soil moisture response time method, we compared preferential flow occurrence between a shale site (Shale Hills, silt loam soils) and a sandstone site (Garner Run, sandy loam soils) at four hillslope positions: ridge‐top, North‐ and South‐facing mid‐slopes and toe slope, for over 2 years. The catchments are neighbouring and covered by temperate forest. For the four hillslope positions, Shale Hills had higher preferential flow frequencies compared to Garner Run. Between these two catchments, the South‐facing mid‐slope sites showed the highest contrasts in preferential flow frequency (33.5% of events at Shale Hills vs. 8.8% at Garner Run) while the ridge‐top sites showed the lowest contrasts (18.7 vs. 13.2%). Additionally, over the unfrozen period, for seven out of eight monitoring sites, drier antecedent conditions tended to be more favourable for preferential flows to occur, with significant ( p < .01) relationships at two sites. Except for the South‐facing mid‐slope sites, both Shale Hills and Garner Run had two preferential flow pathways. The characteristic preferential flow pathways at Shale Hills were the Bw and C horizons, and for Garner Run, preferential flow moved from the E/AE horizon to the Bw horizon. This study shows that shale‐derived soils tended to have higher preferential flow occurrence than sandstone soils, but hillslope positions exhibit different levels of contrasts. More effort should be paid to study the impact of lithology on preferential flows in the context of land surface modelling and biogeochemical reactions to improve ecosystem services of headwater catchments. Abstract : Using high resolution soil moisture sensors, we captured more preferential flow events in the shale soils compared to the sandstone soils. The underlying mechanism that drives this difference may lie in the special soil structure of the shale catchment. The B horizon for both soils seems to be a hot spot for preferential flows to occur.